SPT6 interacts with NSD2 and facilitates interferon‐induced transcription. Issue 10 (20th May 2018) - Ouda, Ryota; Sarai, Naoyuki; Nehru, Vishal; Patel, Mira C.; Debrosse, Maxime; Bachu, Mahesh; Chereji, Răzvan V.; Eriksson, Peter R.; Clark, David J.; Ozato, Keiko
Abstract : The role of the histone chaperone SPT6 in mammalian cells is not fully understood. Here, we investigated the involvement of SPT6 in type I interferon (IFN)‐induced transcription in murine fibroblasts. In RNA‐seq analysis, Spt6 siRNA attenuates about half of 200 IFN‐stimulated genes (ISGs), while not affecting housekeeping genes. ISGs with high mRNA induction are more susceptible to Spt6 siRNA than those with lower levels of induction. ChIP analysis shows that SPT6 is recruited to highly inducible, Spt6 siRNA‐sensitive ISGs, but not to other siRNA‐insensitive ISGs. Furthermore, SPT6 recruitment is abrogated in cells lacking the histone methyltransferase NSD2. In co‐IP experiments, SPT6 interacts with NSD2. In summary, SPT6 facilitates IFN‐induced transcription, highlighting its critical role in gene activation. Abstract :